Pengaruh Perceived Usefulness, Perceived Security, dan Confirmation Terhadap Kepuasan Pengguna Fintech E-wallet DANA : Studi pada Pengguna E-wallet DANA Kabupaten Kebumen - Hasna, Fiki Nurul; Trifiyanto, Kabul (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2023)
The purpose of this study was to determine the effect of perceived usefulness, perceived security, and confirmation of the customer satisfaction of the Kebumen Regency DANA e-wallet users. The population in this study were DANA e-wallet users of Kebumen Regency. Data was collected using a questionnaire, using a Likert scale. This study took 100 respondents. The data analysis used is the validity and reliability instrument test, the classical assumption test, the multiple linear regression analysis test, the hypothesis test, and the coefficient of determination test. The data processing tool uses SPSS 25.0 for Windows. The results of this study show that perceived usefulness affects user satisfaction. Perceived security does not affect user satisfaction. Confirmation effect on user satisfaction. And jointly perceived usefulness, perceived security, and confirmation affect the satisfaction of users.